Liver 2019
DOI: 10.1136/gutjnl-2019-bsgabstracts.200
|View full text |Cite
|
Sign up to set email alerts
|

OTU-09 Use of early-TIPSS in patients with oesophageal variceal bleeding, a UK dual-centre randomised control trial

Abstract: transplantation. Murine models of acute liver injury are characterised by changes in the hepatic macrophage compartment, with an initial accumulation of pro-inflammatory Ly6C hi monocytes and loss of Kupffer cells, followed by the dominance of recruited pro-reparative Ly6C lo macrophages. Current experimental immunomodulatory therapeutics like MC21 and Cenicriviroc inhibit Ly6C hi monocyte recruitment. In non-hepatic sterile injury models IL-4 is known to promote pro-reparative macrophage functions and IL-4 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, endoscopic sclerotherapy was used in more than 5% of patients, which is not in keeping with current international guidelines where VBL is recommended 31 32. A RCT from the UK of early TIPSS in 58 patients with Child-Pugh score ≥8, published in abstract form, showed no difference in survival (HR 1.154 (95%CI 0.3289 to 3.422); P 0.79) nor rebleeding regardless of severity of liver disease or active bleeding 33. The 1-year transplant-free survival in the control arm was significantly better than in the 2010 study (76% vs 61%),28 suggesting improvements in overall care of patients with acute variceal bleeding in the past decade, and extrapolation of results from the 2010 study to the present time needs careful consideration.…”
Section: Indications For Tipssmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, endoscopic sclerotherapy was used in more than 5% of patients, which is not in keeping with current international guidelines where VBL is recommended 31 32. A RCT from the UK of early TIPSS in 58 patients with Child-Pugh score ≥8, published in abstract form, showed no difference in survival (HR 1.154 (95%CI 0.3289 to 3.422); P 0.79) nor rebleeding regardless of severity of liver disease or active bleeding 33. The 1-year transplant-free survival in the control arm was significantly better than in the 2010 study (76% vs 61%),28 suggesting improvements in overall care of patients with acute variceal bleeding in the past decade, and extrapolation of results from the 2010 study to the present time needs careful consideration.…”
Section: Indications For Tipssmentioning
confidence: 98%
“…However, the authors concluded that further study was required to identify factors associated with poor prognosis after early TIPSS. Moreover, the recent RCTs by Lv et al and Dunne et al were not included 30 33…”
Section: Indications For Tipssmentioning
confidence: 99%
“…(1)(2)(3) The early preemptive placement of transjugular intrahepatic portosystemic shunt (TIPS) has emerged as a very effective strategy to improve outcomes in selected populations. (4)(5)(6)(7)(8)(9)(10)(11) Until now, it has been clear that the application of early TIPS is justified in patients with Child-Pugh C (<14 points) cirrhosis and not necessary in those with Child-Pugh A class. (5,7,12,13) Nevertheless, the optimal candidates for early TIPS in Child-Pugh B cirrhosis remain under debate.…”
mentioning
confidence: 99%
“…Unusually, this occurred without a statistically significant increase in hepatic encephalopathy in the TIPSS group. A recent publication from China identified a survival benefit,10 but a Scottish randomised controlled trial did not 11. As these findings are controversial, more studies are required to convincingly demonstrate a survival benefit of early TIPSS.…”
Section: Transjugular Intrahepatic Portosystemic Shuntmentioning
confidence: 98%